2019
DOI: 10.1038/s41598-019-49877-5
|View full text |Cite
|
Sign up to set email alerts
|

Statin use and the risk of colorectal cancer in a population-based electronic health records study

Abstract: There is extensive debate regarding the protective effect of 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) on colorectal cancer (CRC). We aimed to assess the association between CRC risk and exposure to statins using a large cohort with prescription data. We carried out a case-control study in Catalonia using the System for Development of Primary Care Research (SIDIAP) database that recorded patient diseases history and linked data on reimbursed medication. The study included 25 811 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Conversely, a recent case-control study performed in Catalonia showed no significant decrease of CRC risk associated to any statin exposure. When stratification was performed by cancer site, reduction of rectal cancer risk was seen in statin users (OR: 0.87, 95% CI: 0.81–0.92) [ 107 ]. Overall, the role of statins in relation to the incidence of CRC seems to be still controversial and, to date as data suggest, only a weak action as a chemopreventive agent [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a recent case-control study performed in Catalonia showed no significant decrease of CRC risk associated to any statin exposure. When stratification was performed by cancer site, reduction of rectal cancer risk was seen in statin users (OR: 0.87, 95% CI: 0.81–0.92) [ 107 ]. Overall, the role of statins in relation to the incidence of CRC seems to be still controversial and, to date as data suggest, only a weak action as a chemopreventive agent [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…MVA biosynthetic pathway is considered a potential drug target to improve therapeutic window in cancer ( 11 ) ( Figure 4 ). However, despite mounting body of preclinical and epidemiological evidences suggesting MVA pathway inhibitors (i.e., statins) as anticancer agents, many patients remained non-responsive to drug treatment in some cancer clinical trials ( 13 , 20 , 23 , 30 , 33 , 186 ). This is, in part, because cancer cell selectivity, as well as predictive biomarkers of drug efficacy and drug resistance, is still poorly understood.…”
Section: Efficacy and Resistance To Mva Pathway Inhibitors In Human Tmentioning
confidence: 99%
“…Despite clinical evidences supporting the use of MVA pathway inhibitors (i.e., statins) for limiting cancer morbimortality are relatively low, increasing preclinical (11)(12)(13)(14)(15)(16)(17)(18)(19) and epidemiological (20)(21)(22)(23)(24)(25)(26)(27)(28) studies sustain the inverse association between statins and cancer-specific mortality rate. This beneficial effects of statins have been described in several types of cancer, including osteosarsocoma/chondrosarcoma (16)(17)(18), prostate (24,26), colon (29,30), breast (19,31), liver (32,33), pancreas (34), ovarian (35,36), esophageal (37,38), lung (39), and hematological malignances (40). Interestingly, statins may suppress epithelialmesenchymal transition (EMT) program together with the inhibition of cancer stem cell generation, maintenance, and expansion (6,41).…”
Section: Introductionmentioning
confidence: 97%
“…25). Study design has already been published (26,27). Briefly, SIDIAP database comprises clinical information routinely collected by primary care professionals, hospital admissions, and dispensed prescriptions since 2005.…”
Section: Data Sourcementioning
confidence: 99%